Analisis Faktor-Faktor yang Dominan Menentukan Minat Generasi Millenial di Kota Denpasar dalam Menggunakan Mobile Banking - Sania, Maulida Muvidatus (Warmadewa Economic Development Journal (WEDJ), 2024)
There are many factors that influence the interest in using mobile banking among millennials in the city of Denpasar. One of them is the increasing number of merchants and shopping places frequently visited by millennials that provide non-cash transaction payment methods. The aim of this study is to determine the dominant factors that determine millennials in using mobile banking. This study uses primary data with Exploratory Factor Analysis techniques. The data to be processed using SPSS For Windows. The data analysis technique used is exploratory factor analysis, this analysis is used because the researcher does not yet have knowledge or theory or a hypothesis that organizes the structure of the factors to be formed, so this technique helps to build a new theory. From the analysis, it was found that there are 4 factors that influence the interest of millennials in using mobile banking, including Efficiency and Effectiveness of Mobile Banking, Security, Product Variation and Commitment of the Service Provider Bank, and Service Quality.